2013
DOI: 10.1016/j.peptides.2013.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of corticotropin-releasing factor and urocortin 2/3 mRNA by leptin in hypothalamic N39 cells

Abstract: Corticotropin-releasing factor (CRF) activates the pituitary-adrenal axis during stress, and shows anorectic effects via CRF type 1 receptors in the hypothalamus.Both urocortin (Ucn) 2 and Ucn3 also act as anorectic neuropeptides via CRF type 2 receptors. Leptin, a product of the obesity gene secreted mainly from adipose tissue, reduces food intake and increases energy expenditure. A possible interaction between leptin and CRF/Ucns has been suggested, as leptin can regulate expression and activation of CRF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 72 publications
1
7
1
Order By: Relevance
“…Leptin is involved in the regulation of corticotropin releasing factor (CRF). Some have reported that increases in leptin lead to increases in CRF [47,48]. Furthermore, elevated levels of CRF can increase anxiety-like behaviors in rodent models (See Ref.…”
Section: What May Be Driving Increases In Anxiety-like Behaviors?mentioning
confidence: 99%
“…Leptin is involved in the regulation of corticotropin releasing factor (CRF). Some have reported that increases in leptin lead to increases in CRF [47,48]. Furthermore, elevated levels of CRF can increase anxiety-like behaviors in rodent models (See Ref.…”
Section: What May Be Driving Increases In Anxiety-like Behaviors?mentioning
confidence: 99%
“…Central treatment with leptin increases CRF mRNA expression in the PVN . On the other hand, the subcutaneous leptin osmotic minipump decreases CRF mRNA in the PVN of genetically obese ( ob/ob ) mice .…”
Section: Discussionmentioning
confidence: 98%
“…It has been proposed that CRF mediates the increase of energy expenditure through the activation of the sympathetic nervous system (35) and the inhibition of gastric emptying (8). Central treatment with leptin increases CRF mRNA expression in the PVN (36)(37)(38). On the other hand, the subcutaneous leptin osmotic minipump decreases CRF mRNA in the PVN of genetically obese (ob/ob) mice (39).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis was conducted following the protocol described by Yamagata et al, with minor modifications. 22 Protein expression of phosphorylated STAT3/STAT3 in AtT20 cells was assessed by Western blot analysis. After being washed twice with phosphate-buffered saline, cells were lysed with Laemmli sample buffer and centrifuged to remove cell debris.…”
Section: Methodsmentioning
confidence: 99%